2020
DOI: 10.1002/bmb.21396
|View full text |Cite
|
Sign up to set email alerts
|

Rapid deployment of smartphone‐based augmented reality tools for field and online education in structural biology

Abstract: Structural biology education commonly employs molecular visualization software, such as PyMol, RasMol, and VMD, to allow students to appreciate structure-function relationships in biomolecules. In on-ground, classroombased education, these programs are commonly used on University-owned devices with software preinstalled. Remote education typically involves the use of student-owned devices, which complicates the use of such software, owing to the fact that (a) student devices have differing configurations (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…In a similar study, mobile phones use was found to enhance learning outcomes 31 . In accordance with our scope, many studies have addressed this concept 23,30,32,39,40 . Students performance has improved and their GPA indicates the high impact of applying such methods in teaching, especially challenging subjects such as biochemistry.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In a similar study, mobile phones use was found to enhance learning outcomes 31 . In accordance with our scope, many studies have addressed this concept 23,30,32,39,40 . Students performance has improved and their GPA indicates the high impact of applying such methods in teaching, especially challenging subjects such as biochemistry.…”
Section: Discussionsupporting
confidence: 61%
“…31 In accordance with our scope, many studies have addressed this concept. 23,30,32,39,40 Students performance has improved and their GPA indicates the high impact of applying such methods in teaching, especially challenging subjects such as biochemistry. Student perceptions revealed that applications were an effective and innovative tool for learning during the COVID-19 period, based on previous trials of smartphone use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students are easier to understand without having to do experiments in the laboratory, they can do it in arranging the contents that the teacher wants to emphasize. The learning seems interesting as if students see an imagined object directly in 3D, increasing student motivation in doing online learning [41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are now numerous examples of AR applications (AR apps) in science and engineering education. In biology, AR apps are frequently used to represent and explore virtual models of biomolecular functions and relationships [13,14] or anatomical structures [15][16][17]. Additionally, AR can visualize representations of the biological levels of organization from macroscopic to submicroscopic phenomena [18].…”
Section: Introductionmentioning
confidence: 99%